2012
DOI: 10.1177/0269881111430746
|View full text |Cite
|
Sign up to set email alerts
|

Guanfacine effects on stress, drug craving and prefrontal activation in cocaine dependent individuals: preliminary findings

Abstract: Cocaine dependence is associated with increased stress and drug cue-induced craving and physiological arousal but decreased prefrontal activity to emotional and cognitive challenge. As these changes are associated with relapse risk, we investigated the effects of α2 receptor agonist guanfacine on these processes. Twenty-nine early abstinent treatment-seeking cocaine dependent individuals were randomly assigned to either daily placebo or guanfacine (up to 3 mg) for four weeks. In a laboratory experiment, all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 120 publications
6
98
0
1
Order By: Relevance
“…Consistent with our initial laboratory project assessing the effects of guanfacine on stress-and cue-induced cocaine craving (Fox et al, 2012), the current dosing schedule was shown to be safe and well tolerated in both males and females. Side effects were reported in 46.7% of guanfacine males, 66.7% of guanfacine females, 85.7% of placebo females, and 33.3% of placebo males.…”
Section: Safety and Tolerabilitymentioning
confidence: 58%
See 1 more Smart Citation
“…Consistent with our initial laboratory project assessing the effects of guanfacine on stress-and cue-induced cocaine craving (Fox et al, 2012), the current dosing schedule was shown to be safe and well tolerated in both males and females. Side effects were reported in 46.7% of guanfacine males, 66.7% of guanfacine females, 85.7% of placebo females, and 33.3% of placebo males.…”
Section: Safety and Tolerabilitymentioning
confidence: 58%
“…Similarly, in humans, lofexidine has been shown to decrease stress-and drug cue-related opiate craving in opiate dependent individuals also treated with naltrexone (Sinha et al, 2007b). Moreover, in a recent preliminary study, we showed that guanfacine decreased cue-related cocaine craving, anxiety, and arousal in individuals with cocaine dependence (Fox et al, 2012).…”
Section: Introductionmentioning
confidence: 56%
“…In rodent and nonhuman primate models, central delivery of norepinephrine (Brown et al, 2011) or activation of central noradrenergic neurotransmission via antagonism of ␣ 2 adrenergic receptors (Lee et al, 2004;Feltenstein and See, 2006) reinstates extinguished cocaine seeking. Likewise, functional antagonism of noradrenergic neurotransmission through the administration of ␣ 2 adrenergic receptor agonists blocks stress-induced reinstatement in preclinical models (Erb et al, 2000) and attenuates stress-induced craving in human cocaine addicts (Jobes et al, 2011;Fox et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because prazosin, on its own, had no effect on cue-induced reinstatement in rodents, the lack of effect in the monkey cocaine 1 cue reinstatement paradigm is not entirely surprising. The only human studies germane to this subject found that clonidine and guanfacine decreased stress-or cue-induced craving for cocaine (Jobes et al, 2011;Fox et al, 2012).…”
Section: Self-administrationmentioning
confidence: 99%
“…On the basis of recent studies implicating NE in relapse-like behavior, interest in the contribution of this neurotransmitter to addictive processes has reemerged (Weinshenker and Schroeder, 2007;Gaval-Cruz and Weinshenker, 2009). Some noradrenergic compounds have already shown promise in human laboratory studies and initial clinical trials (Gaval-Cruz and Weinshenker, 2009;Fox et al, 2012;Haile et al, 2012;Newton et al, 2012;Shorter et al, 2013;K. Cunningham, personal communication).…”
Section: Introductionmentioning
confidence: 99%